Anti-Windup Methods For Linear Dynamic Systems - Kozubík, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
The aim of this work is to introduce integrator windup and methods of its compensation. Presented methods are Internal Model Control(IMC) and design based on solving linear matrix inequalities (LMI).
Keywords: MIMO systems; integral windup; LMI